L’agglomération de Briga (Eu, Bois-l’Abbé, Seine-Maritime) : premières données sur l’occupation durant l’Antiquité tardive - Étienne Mantel; Stéphane Dubois (Gallia)
Briga was an important roman small town at least 65 ha wide in the south-western province of Gallia Belgica. It was largely deserted in the last decades of the 3rd c. AD, maybe in an organised way especially with several deposits that may mark the official closing of public monuments. During the Late Antiquity, human presence maintained only around the monument called Bâtiment Est, on a small area of ca. 0.25 ha. It was linked with the dimantling of the monumental complex, the recovery of buildings materials. Such an activity gradually declines and seems very tenuous after the middle of the 4th c., even if it survives punctually until the 8th or 9th c. The crisis observed on this site in the 280’s is not limited to Briga: this phenomenon concerns during during Late Antiquity the french coast of the Channel from the Seine to the Bresle estuary, where the previous network of roman occupation (small towns and rural establishments) is disorganised by massive abandonment of settlements.